New technology and management techniques could lift European aquaculture industry. (Research'eu results magazine)
Aquaculture is a booming industry, but growth in Europe is falling behind the rest of the world. One EU-funded project has developed new concepts and technology that could turn this around by triggering sustainable growth in European aquaculture.